PENINGKATAN PRODUKSI DAN KUALITAS JERAMI SORGUM MANIS DENGAN PEMBERIAN PUPUK ORGANIK DAN FOSFAT DARI SUMBER YANG BERBEDA - N.A.S.H Winata; Dwi Retno Lukiwati; E.D. Purbajanti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2014)
Sorghum is an alternative crop for food and feed. The use of sorghum as food includes seeds and sorghum juices. Sorghum plants by products can be used ruminant feed like's sorghum straw. The use of fertilizer in the planting is a major factor in deciding the production. The high price of fertilizer for example SP36 makes constraints in sorghum planting. The use of alternative fertilizers such as rock phosphate can be used instead of SP36. Phosphate rock has an acid soluble, that its use needs to be done a certain process to increase the solubility in water. Decomposition process in the manufacture of manure produce organic acids. Mixed phosphate rock with manure during the decomposition process can increase the solubility of phosphate (P). The use of biochar is used as land amandement, because of its improved physical properties soil. The study was conducted in March 2013-January 2014 at the Faculty of Animal Husbandry and Agriculture land, Laboratory of Ecology and Crop Production Livestock and Agriculture Faculty Diponegoro University. Research materials to be used are seeds of sweet sorghum SEAMEO BIOTROP Bogor, 220m2 land area used consists of 30 plots each measuring 3mx2m with a spacing of 50cmx25cm. The use of manure and manure